2017
DOI: 10.1016/j.semarthrit.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Erosive osteoarthritis: A systematic analysis of definitions used in the literature

Abstract: Background: Erosive osteoarthritis (EOA) is a commonly invoked diagnosis representing an important variant of hand osteoarthritis (OA). There is increasing literature on the prevalence, risk factors, etiology, and management of EOA. Methods: We systematically reviewed the literature to assess variability in the diagnostic definitions used to define EOA in these studies. Results: We reviewed 336 articles and found 62 articles citing diagnostic definitions for EOA. Radiographic appearance was the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 68 publications
(17 reference statements)
0
18
0
4
Order By: Relevance
“…Osteoarthritis is a degenerative joint disease characterized by cartilage deterioration, with proliferative reaction of the subchondral bone and inflammation of the synovial membrane. 1,2 Chronic nociceptive joint pain (>3 months duration) is the most common symptom of osteoarthritis, and one of the most frequent causes of disability, and therefore osteoarthritis is a substantial public health problem. 3 Studies show chronic pain affects 10-30% of European adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis is a degenerative joint disease characterized by cartilage deterioration, with proliferative reaction of the subchondral bone and inflammation of the synovial membrane. 1,2 Chronic nociceptive joint pain (>3 months duration) is the most common symptom of osteoarthritis, and one of the most frequent causes of disability, and therefore osteoarthritis is a substantial public health problem. 3 Studies show chronic pain affects 10-30% of European adults.…”
Section: Introductionmentioning
confidence: 99%
“…Pain and disability associated with osteoarthritis have a negative effect on the perceived quality of life and are one of the main causes of work absenteeism, causing substantial health and non-health costs (temporary or permanent disability) for the Spanish National Health System (NHS) and society. 1,4,8 The therapeutic approach includes non-pharmacological measures, pharmacological treatments, and joint replacement surgery in the most disabling cases. 2,9 Opioids are a pharmacological group characterized by a selective affinity for central and peripheral opioid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…HOA is defined by its clinical appearance by the 1990 American College of Rheumatology (ACR) classification criteria . On the other hand, several imaging studies using MRI and ultrasound have shown that HOA can exhibit signs of inflammation such as synovitis and osteitis, which are considered predictors for disease progression .…”
Section: Introductionmentioning
confidence: 99%
“…Так, при использовании магнитно-резонансной томографии воспаление синовиальной оболочки выявляется в 70% случаев, а наличие жидкости в суставе -в 95% [5]. Как и при других ревматических заболеваниях (РЗ) с выраженным воспалительным компонентом, при ОА в сыворотке крови и синовиальной жидкости возможны небольшое повышение концентрации ряда провоспалительных цитокинов, в том числе фактора некроза опухоли (ФНО) α, интерлейкина (ИЛ) 1, ИЛ6, ИЛ17, ИЛ22, снижение уровня противовоспалительных цитокинов, включая ИЛ10, а также развитие адаптивных иммунных клеточных реакций в тканях сустава, хотя и в ограниченном масштабе [4,[6][7][8][9][10]. При гистологическом исследовании у лиц с ОА в синовиальной оболочке определяются разнообразные изменения, характерные для хронического воспаления: ее утолщение, инфильтрация клетками воспаления, прежде всего мононуклеарами, и различная степень фиброза, причем в некоторых случаях картину инфильтрации синовиальной оболочки монононуклеарами бывает трудно отличить от наблюдаемой при ревматоидном артрите (РА), хотя при ОА эти инфильтраты более локальны, имеют несколько иной клеточный состав, чаще располагаются в местах прикрепления синовии к кости [3,[11][12][13].…”
unclassified
“…У некоторых пациентов развивается особая форма заболеванияэрозивный ОА (ЭОА), для которого типично поражение суставов кистей с выраженным воспалительным компонентом и образованием эрозий. Как правило, ЭОА сопровождается острой болью, различной степенью скованности, припухлости и иногда покраснением сустава, что напоминает симптомы РА, псориатического или микрокристаллического артрита [7]. Неблагоприятное течение ЭОА, для которого характерна высокая локальная воспалительная активность, заставляет врачей искать новые терапевтические подходы.…”
unclassified